2021
DOI: 10.3389/fpsyt.2021.640377
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Adverse Drug Reaction-Related Parameters in Children and Adolescents Treated With Antipsychotic Drugs in Psychiatric Outpatient Clinics

Abstract: Aim: To assess the frequency of monitoring of adverse drug reaction (ADR) related parameters in children and adolescents treated with antipsychotic drugs in psychiatric outpatient clinics and the considerations when monitoring was not performed.Methods: This retrospective follow-up study included 100 randomly selected outpatients aged ≤18 years who had a first prescription of an antipsychotic drug recorded in the electronic medical records of psychiatric outpatient clinics between 2014 and 2017. They were foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A monitoring instruction was defined as an instruction on measuring a physical, laboratory or observational ADR-related parameter before or during antipsychotic drug treatment. In total, 13 ADR-related parameters were included, based on the cardiometabolic, endocrine and extrapyramidal ADRs that can be caused by antipsychotic drugs 13 14. The physical parameters included were weight, height, BMI, waist circumference, blood pressure, pulse and ECG.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A monitoring instruction was defined as an instruction on measuring a physical, laboratory or observational ADR-related parameter before or during antipsychotic drug treatment. In total, 13 ADR-related parameters were included, based on the cardiometabolic, endocrine and extrapyramidal ADRs that can be caused by antipsychotic drugs 13 14. The physical parameters included were weight, height, BMI, waist circumference, blood pressure, pulse and ECG.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, previous studies have shown that the monitoring of children treated with antipsychotic drugs is suboptimal and improved only marginally after the introduction of monitoring instructions provided in the CPGs. [12][13][14] To enable the implementation of the monitoring instructions provided in the CPGs in daily clinical practice, first, the quality of the CPG is important, for example, the clarity of presentation. Second, each monitoring instruction included in the CPG has to be easily identifiable, clear, unambiguous and easy to apply.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation